(untitled) (International Journal of Politics & Social Sciences Review (IJPSSR), 2026)
The main purpose of this study Effects of social support and self-efficacy on stress management among physical education teachers working at secondary schools of District Dera Ismail Khan. Therefore, the cross-sectional approached employed by the researcher. The Data were collected from 495 male and female physical education teachers selected through stratified random sampling. Standardized instruments were used to measure perceived social support, self-efficacy, and stress management, and the data were analyzed using Statistical Package for Social Sciences (SPSS Version-32) For the data analysis the researcher were used Statistical tools descriptive statistics, correlation, regression, t-tests, and ANOVA. On the basis of results, the findings Found that the teachers reported moderate to high levels of social support, self-efficacy, and stress management. Significant positive relationships were found between social support and stress management, as well as between self-efficacy and stress management, with self-efficacy emerging as the stronger predictor. Multiple regression analysis confirmed that both variables independently and jointly contributed to effective stress management. Demographic factors such as gender, teaching experience, and educational level showed significant variations, while ethnicity did not influence the study variables. On the basis of results, this study highlighted that Social Support and Self-Efficacy has significance impact upon Stress Management among Physical Education Teachers working at Secondary School Level.